Membranous cataract – a case report - Zawistowska, Joanna; Bakunowicz-Łazarczyk, Alina; Romanowska-Dixon, Bożena; Karska-Basta, Izabella (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
Presentation of a rare case of an 8-week-old infant with unilateral congenital cataract and microphtalmia. The child underwent an ophthalmic examination under general anesthesia and an ultrasound assessment in A- and B-scan modes. The patient met the eligibility criteria for cataract phacotomy and phacoaspiration surgery. Most of the resorbed nuclear cortex of the lens and the fibrous membrane with blood vessels in the posterior lens capsule were found intraoperatively. They were closed by endodiathermy and an opening was made in the membrane to keep the visual axis clear. The procedure was complicated by bleeding from the pathological blood vessels in the iris during peripheral iridectomy.